Histochemical detection of the secretion of superoxide radicals and hydrogen peroxide by age-1 mutants of Neurospora - K. D. MUNKRES (Fungal Genetics Reports, 1990)
The Age-1 gene family consists of 16 functionally redundant, closely linked loci on linkage group I. (Munkres 1985 Superoxide Dismutases, Vol. III, CRC Press, Boca Raton, FL). Dominant mutations at those loci reduce conidial lifespan (loc. cit.) and cause multiple deficiencies of at least 12 antioxidant enzymes; the endocellular superoxide dismutases (SOD), and exocellular cell wall bound SOD isozyme, catalase, peroxidases and reductases (Munkres et al. 1984 Mech. Age. Dev. 24:83-100; Munkres 1990 Free Radical Bio. Med., in press). Colonies of the mutants secrete superoxide radicals and H2O2, apparently as a consequence of their antioxidant enzyme deficiencies. The purpose of this note is to describe histochemical methods that detect the secretions.